Sophisticated Surveillance—Intolerable Intrusion or Prudent Protection? - William H. Webster (Washington University Law Review, 1985)
I propose to talk about some of the measures we legitimately can employ in a free society to protect ourselves from the ravages of crime, of terrorism, of betrayal of the public trust. Our basic liberties are identified and enshrined in our Constitution. There must be no retreat from that. An awareness of and respect for the law's demands is fundamental to all who are sworn to uphold the law. But it is no defense of ordered liberty to deny to those whom we commission to enforce the laws the lawful tools that modern science and professional advancement have made possible. There is a balancing process which each of us must share. We call it "justice" and it continues to be the great interest of man on earth.
Keywords: Criminal investigation